2002
DOI: 10.1038/nn809
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of cold thermotransduction is determined by differential ionic channel expression

Abstract: Sensations of cold are mediated by specific thermoreceptor nerve endings excited by low temperature and menthol. Here we identify a population of cold-sensitive cultured mouse trigeminal ganglion neurons with a unique set of biophysical properties. Their impulse activity during cooling and menthol application was similar to that of cold thermoreceptor fibers in vivo. We show that cooling closes a background K+ channel, causing depolarization and firing that is limited by the slower reduction of a cationic inwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
318
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(346 citation statements)
references
References 44 publications
26
318
2
Order By: Relevance
“…However, a number of laboratories interested in cold transduction began to use primary cultures of either DRG or TG neurons as in vitro models of sensory afferents. Approximately 10% respond to cold temperatures, with thresholds for activation below 30°C, and almost all of these sensory neurons are menthol-sensitive as well [47,71,78,79]. Thus, these in vitro data support the hypotheses of Hensel and Zotterman in that it seemed likely that cold and menthol work through a similar mechanism, leading to the search for their common molecular site of action.…”
Section: The Hot Of Capsaicin and The Cool Of Mentholsupporting
confidence: 71%
See 1 more Smart Citation
“…However, a number of laboratories interested in cold transduction began to use primary cultures of either DRG or TG neurons as in vitro models of sensory afferents. Approximately 10% respond to cold temperatures, with thresholds for activation below 30°C, and almost all of these sensory neurons are menthol-sensitive as well [47,71,78,79]. Thus, these in vitro data support the hypotheses of Hensel and Zotterman in that it seemed likely that cold and menthol work through a similar mechanism, leading to the search for their common molecular site of action.…”
Section: The Hot Of Capsaicin and The Cool Of Mentholsupporting
confidence: 71%
“…It is a biochemical axiom that cold temperatures hamper protein function, and this inhibitory property of cold has been suggested to be a mechanism for neuronal depolarization. A number of studies have suggested that cold inhibition of background K + conductances or the Na + /K + -ATPase leads to membrane depolarization of cold-sensitive afferents [78,[108][109][110]. In the former example, the K + -channel TREK-1 is strongly inhibited by cooling in vitro and expressed very highly in sensory neurons [111].…”
Section: Other Thermosensory Processesmentioning
confidence: 99%
“…However, behavioral studies with TRPM8-null mice show that TRPM8 does serve a role in noxious cold sensing, but that it is likely not the sole determinant (Bautista et al, 2007;Colburn et al, 2007;Dhaka et al, 2007). Moreover, functional data from cultured sensory neurons show that approximately one-half of menthol-sensitive neurons are also capsaicinsensitive, suggesting coexpression of both TRPM8 and TRPV1 in this subset of cold-and menthol-sensitive neurons (McKemy et al, 2002;Viana et al, 2002;Hjerling-Leffler et al, 2007). Last, in primary culture, a subset of menthol-sensitive DRG neurons has been shown to have nociceptive properties (Xing et al, 2006).…”
Section: Trpm8 Is Expressed In Both Nociceptive and Non-nociceptive Smentioning
confidence: 99%
“…While there has been significant recent progress in defining the means by which peripheral neurons detect heat stimuli (Caterina and Julius 2001;Peier et al 2002b;Smith et al 2002;Souslova et al 2000;Xu et al 2002), the molecular mechanisms underlying the detection of cool and painfully cold stimuli remain less well understood. Cooling-evoked changes in membrane potential, ionic conductance, or intracellular calcium can be recapitulated in sensory neurons cultured from dorsal root (DRG) and trigeminal ganglia (TG) (McKemy et al 2002;Okazawa et al 2002;Flonta 2001a,b, 2002;Suto and Gotoh 1999;Thut et al 2003;Viana et al 2002). Data from several recent electrophysiological studies have revealed two general mechanisms that appear to underlie cold transduction in these neurons.…”
Section: Introductionmentioning
confidence: 99%
“…One mechanism involves the cooling-induced activation of a nonselective cationic current that is present in approximately 10% of cultured sensory neurons (Okazawa et al 2002;Flonta 2001a, 2002) and can be potentiated by the cooling agent menthol Flonta 2001a, 2002). A second mechanism entails the cooling-induced inhibition of certain potassium currents, which results in net membrane depolarization (Reid and Flonta 2001b;Viana et al 2002). In addition, a distinct potassium current has been reported to mask cooling-induced depolarization in a subset of apparently cold-insensitive sensory neurons (Viana et al 2002).…”
Section: Introductionmentioning
confidence: 99%